Adverse drug reactions. (July 2020) - Ferner, Robin; Pucci, Mark
Abstract: Adverse drug reactions (ADRs) are important but often difficult to diagnose. They should be considered in the differential diagnosis of a wide range of conditions. Estimates of the proportion of acute hospital admissions caused by ADRs range from 0.5% to 12.8%. They can be classified according to dose-relatedness, time course and susceptibility. Toxic effects are caused by high doses, for example nephrotoxicity with aminoglycosides. Collateral effects are encountered within the therapeutic range, as for Clostridioides difficile infection with broad-spectrum antibiotics. Hypersusceptibility reactions, which include anaphylaxis in individuals allergic to penicillins, can occur at doses much lower than therapeutic. Some reactions occur at specific times after exposure. Susceptibility to ADRs differs. Sometimes there are marked differences as a result of genetic variation: drug-induced haemolysis in patients with glucose-6-phosphate dehydrogenase deficiency is an example. Other factors that alter susceptibility to ADRs include age, sex and certain disease states. The detection of ADRs relies heavily on spontaneous reporting (e.g. the UK Yellow Card scheme), stimulated post-marketing surveillance and case–control studies. Licensing authorities can then take steps to mitigate the effects of newly detected reactions. Detecting and reporting ADRs makes prescribing safer and more likely to achieve its aims.